PID-LQR Combined Linear Controller for Balancing Ballbot: Simulation and Experiment - Nguyen, Van-Dong-Hai; Cu, Minh-Phuoc; Nguyen, Tran-Minh-Nguyet; Huynh, Thanh-Do; Dang, Dinh-Khoi; Hoang, Tan-Dat; Nguyen, Minh-Quan; Vu, Dinh-Dung; Le, Chi-Hai-Duong; Phan, Nguyen-Bao-Long; Bui, Quoc-Duy; Le, Ngoc-Hai; Vo, Duy-Phuc (Peneliti Teknologi Teknik Indonesia, 2023)
Ballbot is a robotic structure in which the robot self-balances on a ball by rotating wheels. This robot is a popular form of service robot. Developing controllers for this system provides academic tools for reality. In this paper, after presenting the dynamic equations of the ballbot, we design a Proportional Integrated Derivative (PID)-Linear Quadratic Regulator (LQR) combined (PID-LQR) controller to balance the robot on the ball. The simulation results show the success of this method. An experimental model of a ballbot is presented. In the experiment, PID-LQR combined controller also shows its ability to self-balancing for the ballbot. With this finding, a method of controlling this model is a reference for developing this service robot.